Venomous mollusks: the risks of human accidents by conus snails (gastropoda: conidae) in Brazil - Haddad Júnior, Vidal [UNESP]; Paula Neto, João Batista de; Cobo, Válter José (Sociedade Brasileira de Medicina Tropical - SBMT, 2006)
Os moluscos do gênero Conus apresentam um aparato venenoso composto de uma rádula quitinosa ligada a glândulas de peçonha, causando envenenamentos humanos graves e mesmo óbitos pela ação neurotóxica indutora do bloqueio de vários receptores e paralisia muscular. Não há casos descritos de envenenamento no país, mas determinadas populações correm risco de acidentes.

Mollusks of the genus Conus present a venomous apparatus composed of radulae, a chitin structure linked to glands, which injects potent neurotoxic peptides, causing serious human envenomation and even death, associated with the blockage of certain receptors and muscular paralysis. No reported envenomation has occurred in Brazil, but certain populations are at risk of accidents.
Moluscos peçonhentos: riscos de acidentes em humanos pelo molusco Conus (Gastrópode: cunidae) in Brazil
Keywords: Conus; Animais peçonhentos; Moluscos venenosos; Envenenamentos humanos; Brasil; Conus; Venomous animals; Venomous mollusks; Human envenoming; Brazil